2012
DOI: 10.1074/jbc.m111.335174
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 4 Is Required for Maturation of Photoreceptor Cells

Abstract: Background:The essentiality of an antioxidant enzyme for the development and maturation of photoreceptor cells has remained unclear. Results: While GPx4-abrogated photoreceptor cells develop and differentiate into rod and cone cells, their outer segments are structurally disorganized and they undergo rapid apoptosis in vivo. Conclusion: GPx4 is essential for the maturation of photoreceptor cells. Significance: A novel role of an antioxidant enzyme for photoreceptor cells is disclosed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 30 publications
3
68
1
1
Order By: Relevance
“…Systemic deletion of Gpx4 in mice causes embryonic lethality, which was not observed when other Gpx genes were deleted (Ran et al, 2004), suggesting a unique role for Gpx4 in physiology. Four groups independently created conditional Gpx4 knockout mice and analyzed the cell death mechanisms after Gpx4 inhibition (Seiler et al, 2008; Sengupta et al, 2013; Ueta et al, 2012; Yoo et al, 2012). Lipid peroxidation was observed in all knockout models, highlighting the importance of Gpx4 for protecting cells from detrimental effects of lipid peroxides.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic deletion of Gpx4 in mice causes embryonic lethality, which was not observed when other Gpx genes were deleted (Ran et al, 2004), suggesting a unique role for Gpx4 in physiology. Four groups independently created conditional Gpx4 knockout mice and analyzed the cell death mechanisms after Gpx4 inhibition (Seiler et al, 2008; Sengupta et al, 2013; Ueta et al, 2012; Yoo et al, 2012). Lipid peroxidation was observed in all knockout models, highlighting the importance of Gpx4 for protecting cells from detrimental effects of lipid peroxides.…”
Section: Discussionmentioning
confidence: 99%
“…70 A recent study has shown that GPx4 plays an important protective role for photoreceptor cells against oxidative stress. 71 GPx6 is a close homolog of plasma GPx3. Compared to other GPx proteins, GPx6 was identified rather late because its mouse and rat orthologs had Cys in place of SeCys.…”
Section: Glutathione Peroxidasesmentioning
confidence: 99%
“…9 Of importance, Gpx4 is the only glutathione peroxidase known to be essential for embryonic development. 10,11 Moreover, Gpx4 controls caspase-independent cell death in neurons, 12 photoreceptor cells, 13 and T cells. 14 Ferroptosis is a nonapoptotic form of cell death involving the production of iron-dependent ROS.…”
Section: Introductionmentioning
confidence: 99%